(untitled) (International Journal of Physiotherapy, 2017)
Background: There is limited evidence to support the therapeutic effect of Manual Therapy on Hip Osteoarthritis (HOA) patients. The purpose of this study was to investigate whether implementation of weight-bearing mobilization-with-movement (MWM) and auto-mobilization had a significant improvement in pain and functionality after a series of sessions. Methods: Forty patients 50-80 years of age, with HOA, were randomly assigned into two groups. Patients in the treatment group received MWM in standing position and auto-MWM for two weeks, while control patients received a Sham form of MWM. Pain and functionality were measured at baseline, post-treatment and three months’ follow-up,using the Visual Analogue Scale (VAS) and the Lower Extremity Functional Scale (LEFS). Mixed ANOVA was used to examine possible differences between treatment phases and between groups, but also interactions among Group and Time factors. Result: The present findings revealed a significant interaction between factors and significant main effects of each Time and Group factors on pain and functionality. The treatment group showed improved post-MWM VAS and LEFS scores compared to baseline scores (p<.001), and improved follow-up MWM and LEFS scores compared to post-MWM scores (p<0.001). In control group, no significant differences were found on either of the post or follow up VAS and LEFS scores compared to baseline scores (p>.001). Differences between groups were significant in post-treatment and follow-up scores (p<.001). Conclusion: Our findings suggest that weight bearing-MWM and auto-MWM are a significant treatment approach,improving pain and functionality in hip osteoarthritis patients.